Kejahatan Perkosaan Dalam Bingkai Politik Hukum Pidana - Munawir Munawir (Justicia Islamica, 2011)
Criminal act of rape is one type of violent crime to woman. In the development of this crime is no longer seen as solely a moral offence. But inside it has touched on the anger and violence problem which is considered a violation and negation HAM. Based on the development this, planner group new penal code in looking need to quicly change formulation a criminal act of rape. That is no longer the sense as in the formulation Section 28 penal code (WvS), but expanded in accordance with the development and future state. Through political policy or criminal law, formulations have been made a criminal act of rape is more appropriate to contemporary situations and this formula has been placed in section 423 hhe draft new penal code  which is currently awaiting approval from the legistilative assembly.